Análisis sobre elección de ocupaciones que generen empleo usando modelos de elección discreta: Medellín Área Metropolitana 2009 (2011)
The formation and consolidation of businesses is a key element in achieving social and economic transformation of Colombia. Example of this hipotesis, are the increasing number of academic papers and policies to promote entrepreneurship in country and its regions. Therefore, we want to contrast what is observed in the literature applied to the case of Medellin Metropolitan Area in 2009, to contribute to the discussion on the determinants and policy creation and strengthening of companies. the main objective if this paper is know what is the probability that an individual will be an entrepreneur, formal independent,employee or informal independent, being the first state that generates the largest effect on growth and development of the region. We use three discrete choice models such as Logit and Multinomial Probit and Logit Binary sequence, for observing that education, use of information technologies and telecommunications, and financial capital are variables that contribute to the probability to be entrepreneur.